ANALYSIS OF IMĀM MUḤAMMAD'S WORK " MUWAṬṬA’" AND THE CHAPTER OF TAFSFIR IN IT - Akhmedov Burkhan Abdurakhmonovich (Western European Studies, 2024)
The work " Muwaṭṭa’" played an important role in the development of Ḥanafī jurisprudence, and it was compared to the most important books in the school, "Ẓāhir ar- riwāyah ". Because it is one of the valuable works that provide evidence for the Ḥanafī sect. At the same time, it is one of the first published works in the field of comparative jurisprudence. The work is a beautiful example of pure scholarly discussion, and contains many ḥadīths that call for peace and morality that are very relevant today. The work " Muwaṭṭa’" is of great importance in improving the religious-educational and socio-spiritual environment.
Keywords: Muwaṭṭa’; Ẓāhir ar-riwāyah; Ḥanafī